PHOTOMETRIC MONITORING OF SHORT-PERIOD CONTACT BINARIES - Vanko, M. (Одеські астрономічні публікації, 2017)
The first photoelectric B; V light curves of the contact binary FU Dra, as well as new B; V light curves of the contact binaries AH Aur, UV Lyn and YY CrB, obtained at the Stara Lesna and Skalnate Pleso Observatories, are presented. New photometric elements of AH Aur, FU Dra and UV Lyn computed from these light curves were combined with published spectroscopic elements to derive the absolute parameters of the systems.